Thermal conductivity of bimetal Al-Cu: molecular dynamics simulation. (31st January 2022) - Junaidi, Syarif; Badawy, Khaled; Hisham, Mohamed; Hussien, Hussien A.
In this study, phonon thermal conductivity of bimetal Al-Cu was modelled using molecular dynamics. The conductivities of pure Cu and Al were calculated and discussed first to verify the adopted methodology. The behaviour of the heat current autocorrelation function was discussed for pure metals and the bimetal. The values of thermal conductivity at different temperatures for pure metals were reported and the results were correlated to similar computational works. The thermal conductivity was found to drop as the temperature increased. The bimetal Al-Cu thermal conductivity and the variation with temperature were reported. It was found that the bimetal Al-Cu has a very low conductivity compared to pure metals. It was found that the drop in thermal conductivity was due to increase in lattice defects and distortions arising from the bimetal interface. The drop in thermal conductivity as the temperature increases still holds and follows a linear relation.